1989
DOI: 10.1055/s-2007-1024874
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Noninvasive Fiber Type Determination by NMR

Abstract: In vivo 31P NMR spectroscopy was used to determine the ratios of creatine phosphate (PCr) to adenosine triphosphate (ATP) and inorganic phosphate (Pi) in leg and arm muscles of four sprinters, one marathon runner, and two sedentary subjects. Both ratios were definitely higher in the sprinters indicating that, since muscle ATP and Pi concentrations are constant, the PCr muscle content of these athletes is higher than usual. Sprinters are known to have higher percentages of fast-twitch fibers, which are richer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The pH was similar in both groups of athletes. The results principally confirm literature data (1,11,12).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pH was similar in both groups of athletes. The results principally confirm literature data (1,11,12).…”
Section: Discussionsupporting
confidence: 91%
“…BOICELLI et al (1) have found PCr/ATP ratios of 6.7-8.2 in the gastrocnemic muscle of sprint runners. These measurements were performed in 3 sprint runners with best times between 10.6-11.1 s. One of the athletes in that report must be classified as a middle-distance runner.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously cross sectional NMR-studies have compared sprint and endurance trained runners and untrained subjects at rest [11], and it was demonstrated that long distance runners have faster CrP and P i kinetics in recovery after moderate intensity exercise compared to untrained controls [44]. During maximal effort total occlusions of the blood circulation to affected muscles occur, due to increased intra muscular pressure [36].…”
Section: Introductionmentioning
confidence: 98%
“…Several longitudinal studies [1,2,27,29,37,40] have shown that the two training types induce specific adaptations and cross sectional studies have demonstrated that marked qualitative differences may exist in fiber type distribution [16,21] and capillary supply [13,41] between differently trained groups.Previously cross sectional NMR-studies have compared sprint and endurance trained runners and untrained subjects at rest [11], and it was demonstrated that long distance runners have faster CrP and P i kinetics in recovery after moderate intensity exercise compared to untrained controls [44]. During maximal effort total occlusions of the blood circulation to affected muscles occur, due to increased intra muscular pressure [36].…”
mentioning
confidence: 98%